Multimodal Analysis of the Disabled Character Tyrion Lannister in the Game of Thrones Series (2011-2019) - Marbun, Dewi Christina; Irawanto, Budi (Universitas Muhammadiyah Surakarta, 2023)
Media, especially films, have an important role in the construction of people with disabilities. This research examines Tyrion Lannister as a person with a disability represented and constructed in the Game of Thrones series. Tyrion Lannister is interesting because he is the only character born with a disability. This condition differs from others with perfect physical conditions in real life. In this series, Tyrion Lannister shows the body as a social sign. He is represented as a realistic and complex character, not inspiring, not evil, or selling mercy, as the portrayal often used by the media in portraying people with disability. This research uses a qualitative approach with a multimodal critical discourse analysis methodology by Gunther Kress and Theo van Leeuwen. The data is based on seasons and episodes of the Game of Thrones, which relate to Tyrion Lannister as people with a disability, literature study, and documentation. The research found that the representation of Tyrion Lannister is realistic and complex, showing the prejudice and social stigma he has received as a person with a dwarf body.